1997
DOI: 10.1164/ajrccm.155.3.9117000
|View full text |Cite
|
Sign up to set email alerts
|

DNA fingerprinting with two probes decreases clustering of Mycobacterium tuberculosis.

Abstract: DNA fingerprinting of Mycobacterium tuberculosis is used to study the epidemiology of tuberculosis, but the specificity of the widely used IS6110 technique has not been validated. Isolates from Denver, Colorado from December 1988 through June 1994 were fingerprinted with the IS6110 technique. Available records were reviewed for patients whose isolates were within IS6110-defined clusters, and these isolates were fingerprinted with an independent technique (pTBN12). Of 189 isolates, 86 (46%) were in IS6110-defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
72
1
3

Year Published

1998
1998
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 21 publications
6
72
1
3
Order By: Relevance
“…The interpretation that equilibrium has not been reached is also consistent with studies using secondary genetic markers in TB. Although it has been shown that secondary markers allow IS fingerprint clusters to be further differentiated, it is also evident that the states of these markers are correlated with IS genotypes (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation that equilibrium has not been reached is also consistent with studies using secondary genetic markers in TB. Although it has been shown that secondary markers allow IS fingerprint clusters to be further differentiated, it is also evident that the states of these markers are correlated with IS genotypes (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate visual reading of PGRS fingerprints, samples were electrophoresed together on the same gel according to the results with IS6110. As suggested by BURMAN et al [17] only fragments exceeding 1.6 kb were analysed.…”
Section: Comparison Of Rflp Patternsmentioning
confidence: 99%
“…Even though these large urban areas have a high proportion of patients infected with human immunodeficiency virus (HIV), who are known to be more susceptible to in-fections and at greater risk of latent TB infection rapidly progressing to active disease, these figures greatly exceed general assumptions regarding transmission (~10%; [10]). Both studies concentrating on these big cities are based on the assumptions that deoxyribonucleic acid (DNA) fingerprinting using the IS6110 sequence as a probe provides ac-curate typing of M. tuberculosis isolates and, furthermore, that the identification of cluster strains necessarily implies recent transmission.Most recent concepts of molecular epidemiology utilizing additional genetic markers, such as the polymorphic GC-rich repetitive sequence (PGRS; [11,12]) and/or the 36 base pair (bp) direct repeat (DR; [13,14]) have, however, demonstrated that DNA fingerprinting with the IS-6110 technique was not always sufficient, particularly, in those cases where isolates have fewer than six copies of IS6110 [15][16][17]. Use of supplementary fingerprinting techniques markedly decreased clustering and, thus, put the transmission links suggested by molecular biology more in line with epidemiological data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in the study of BURMAN et al [32] (in Denver, USA) 40 of the 51 patients (78%) with clustered isolates had definite or possible epidemiological links identified through contact tracing.…”
mentioning
confidence: 76%